Influence of chronotype, training/competition schedules, and daytime napping on elite athletes sleep - Vitale, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Sleep disturbances in athletes may be explained by their constant exposure to many stressors that impair sleep. Among these variables, also training and competition schedules may influence the sleep response to exercise. Late evening or night competitions, that are very common in team sport disciplines (eg: soccer, basketball or volleyball), can have a negative impact on athletes' sleep onset latency and sleep efficiency. On the contrary, early morning training sessions can reduce total sleep time leading to a sleep debt, especially in athletes of individual sport disciplines (eg. runners, race walkers, triathlon athletes). In addition, athletes have different chronotypes with morning-type athletes displaying early sleep-wake cycles and evening-types athletes showing a strong predisposition toward eveningness. In this context, daytime naps are important tools to offset the adverse impacts of inadequate sleep. Napping during the day can increase the amount of sleep obtained in a 24-hour period and many athletes report including daytime napping in their training program. With the present talk, napping characteristics and the impact of naps on various measures of athletic performance in athletes will be discussed.